Imperialism and global political economy/ by Alex Callinicos. - Callinicos, Alex (Polity, 2009)
In 'Imperialism and Global Political Economy', Alex Callinicos intervenes in one of the main political and intellectual debates of the day. The global policies of the United States in the past decade have encouraged the widespread belief that we live in a new era of imperialism. But is this belief true, and what does 'imperialism' mean?